Kontribusi Mahasiswa Magang MBKM dalam Mendukung Pelayanan Penagihan Pajak Reklame dan Retribusi Kebersihan di BPPRD Kota Palangka Raya - Riskha Fathul Jannah; Haidi Hajar Widagdo; Masriani Wahyu Ningrum (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The MBKM internship program provides students with the opportunity to be directly involved in public service activities within government institutions. Through placement at BPPRD Palangka Raya City, the student was assigned to the service counter for advertisement tax and waste retribution. Activities included recording taxpayer data, scanning documents, archiving files, and delivering tax-related information both in person and digitally. This experience not only enhanced technical understanding and knowledge of tax administration procedures but also developed the student's discipline and communication skills. The presence of the intern contributed to smoother services, particularly in document handling and time efficiency. Overall, the internship provided meaningful learning for the student and offered real support to the institution.